Analisis Usability pada SIAPEL-TEGAS dalam Pengurusan KTP-el dengan Menggunakan Metode System Usability Scale (SUS) - vita mei fudnia watiningsih; Mochammad Anshori; Ahsanun Naseh Khudori (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
SIAPEL-TEGAS (Integrated Population Administration Information System) is a digital service provided by the Department of Population and Civil Registration of Malang City that enables citizens to process population administration documents, including electronic identity cards (e-KTP), online. This study aims to analyze the usability level of the SIAPEL-TEGAS application in e-KTP processing services using the System Usability Scale (SUS) method. Data were collected through an online questionnaire distributed to 50 respondents who had previously used the service, employing a purposive sampling technique. The questionnaire consisted of 10 standard SUS statements measured using a 5-point Likert scale. The results showed that the SIAPEL-TEGAS application achieved an average SUS score of 85.35, which falls into the